2011
DOI: 10.1371/journal.pone.0025564
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypermethylation Mediated Downregulation of FBP1 in Human Hepatocellular Carcinoma and Colon Cancer

Abstract: FBP1, fructose-1,6-bisphosphatase-1, a gluconeogenesis regulatory enzyme, catalyzes the hydrolysis of fructose 1,6-bisphosphate to fructose 6-phosphate and inorganic phosphate. The mechanism that it functions to antagonize glycolysis and was epigenetically inactivated through NF-kappaB pathway in gastric cancer has been reported. However, its role in the liver carcinogenesis still remains unknown. Here, we investigated the expression and DNA methylation of FBP1 in primary HCC and colon tumor. FBP1 was lowly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 12 publications
2
125
2
1
Order By: Relevance
“…Low expression of FBP1 has previously been observed in human hepatocellular carcinoma (HC), colon cancer (CC), breast cancer (BC), gastric cancer (GC) and ccRCC tissues (6,(9)(10)(11). The current data is consistent with the latter study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Low expression of FBP1 has previously been observed in human hepatocellular carcinoma (HC), colon cancer (CC), breast cancer (BC), gastric cancer (GC) and ccRCC tissues (6,(9)(10)(11). The current data is consistent with the latter study.…”
Section: Discussionsupporting
confidence: 92%
“…The current data is consistent with the latter study. The reason for low FBP1 expression in HC, CC, BC and GC has been identified as hypermethylation of the promoter region of the FBP1 gene (9)(10)(11). However, the mechanism of FBP1 inhibition in ccRCC tissues has not been clearly identified and requires further investigation (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FBP1 promoter methylation status was determined using the results of methylation-specific PCR, as described in a previous report (8), or methylation array data from GEO database accession numbers GSE60753 (12) and GSE67485 (13). Data on promoter methylation profiles were available for 7 liver cancer cell lines (Supplementary Table S2).…”
Section: Analysis Of the Cancer Cell Line Encyclopedia Databasementioning
confidence: 99%
“…6) and breast cancer (7). With regard to HCC, in vitro experiments have shown that FBP1 expression is silenced by promoter methylation and that ectopic FBP1 expression inhibits anchorage-dependent growth of a cell line through cell-cycle arrest (8). However, the role of FBP1 in altered glucose metabolism has not been assessed in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether reversing this glycolytic phenotype via gluconeogenesis is beneficial to tumour suppression remains elusive. Furthermore, although normal liver cells continually produce glucose via gluconeogenesis, whether and how those transformed hepatocytes escape the inhibitory effect of gluconeogenesis on glycolysis [19][20][21] remains unclear.…”
mentioning
confidence: 99%